Emergence of waterfowl‐originated gene cassettes in HPAI H7N9 viruses caused severe human infection in Fujian, China. Issue 5 (11th June 2019) - Yang, Lei; Xie, Jianfeng; Zhang, Ye; Zhu, Wenfei; Li, Xiyan; Wei, Hejiang; Li, Zi; Zhao, Lin; Bo, Hong; Liu, Jia; Dong, Jie; Chen, Tao; et al.
Abstract: Background: Highly pathogenic avian influenza (HPAI) A(H7N9) virus emerged and caused human infections during the 2016‐2017 epidemic wave of influenza A(H7N9) viruses in China. We report a human infection with HPAI H7N9 virus and six environmental isolates in Fujian Province, China. Methods: Environmental surveillance was conducted in live poultry markets and poultry farms in Fujian, China. Clinical and epidemiologic data and samples were collected. Real‐time RT‐PCRs were conducted for each sample, and H7‐positive samples were isolated using embryonated chicken eggs. Full genomes of the isolates were obtained by next‐generation sequencing. Phylogenetic analysis and antigenic analysis were conducted. Results: A 59‐year‐old man who raised about 1000 ducks was identified as HPAI H7N9 infection. Six HPAI H7 viruses were isolated from environmental samples, including five H7N9 viruses and one H7N6 virus. Phylogenetic results showed the human and environmental viruses are highly genetically diverse and containing significantly different gene constellation from that of other HPAI H7N9 previously reported. The internal genes derived from H7N9/H9N2, H5N6, and the Eurasian wild‐bird gene pool, indicating waterfowl‐originated genotypes, have emerged in HPAI H7N9/N6 viruses and caused human infection. Conclusion: The new genotypes raise the concern that these HPAI H7 viruses might transmit back into migratory birds and spread to other countries as the HPAI H5Nx viruses. Considering their capability of causing severe infections in both human and poultry, the HPAI H7 viruses in this study pose a risk to public health and the poultry industry and highlight the importance of sustained surveillance of these viruses.